Knowledge structure of natural anaesthetics in aquaculture: a bibliometric analysis - Ahmad Arifin, Syamsul; Fitri Yusof, Muhammad; Jaapar, Muhd Zudaidy; Amatul-Samahah, Md. Ali; Lani, Mohd Nizam (Journal of Academia, 2025)
Aquaculture anaesthesia, particularly with natural agents, has gained increasing attention due to its relevance in fish welfare, stress management, and sustainable aquaculture practices. This study addresses the need to systematically assess the state of knowledge, gaps, and potential future trajectories in this dynamic field. We conducted a bibliometric analysis using Scopus to collect and analyse scholarly publications related to natural anaesthesia in aquaculture. Metrics such as citation counts, coauthorship networks, and keyword co-occurrence were employed to unveil the research landscape. The VosViewer tool was utilised for network visualisations, offering insights into collaboration patterns and thematic clusters. Preliminary findings indicate a prolific output of research, with specific authors and countries playing pivotal roles in shaping the discourse. The co-authorship network analysis reveals key figures and interdisciplinary collaborations, while the keyword co-occurrence analysis uncovers central themes and emerging topics. The country collaboration map provides a visual representation of regional clusters, emphasising the global nature of aquaculture anaesthesia research. This bibliometric study is poised to contribute a holistic understanding of the trends and patterns in natural anaesthesia research for aquatic species. The expected results will shed light on the interdisciplinary nature of the field, identify potential research collaborators, and pinpoint knowledge gaps for future exploration. The insights gained from this study aim to inform researchers, policymakers, and practitioners involved in aquaculture, paving the way for sustainable and welfare-centric practices in the field of aquaculture anaesthesia.